Characterization Of Cassava Flour (Manihot esculenta Crantz) with Combination of Pregelatinization and Fermentation Methods - Hildegardis Vania Santika; Yoga Aji Handoko (Jurnal Sains dan Teknologi Pangan, 2023)
Cassava has a high content of starch that can process into flour. Using a different kind of modification process results in the different characterization of flour that is produced. Physic modification by pregelatinization produced pregel flour. Whereas, enzymatic modification by the fermentation process produced mocaf flour. This research aimed to determine the characterization of cassava flour with a combination of pregelatinization and fermentation methods. This study used a Factorial Randomized Block Design with two factors. The first factor was boiling temperature which is 65oC and 80oC whereas the second factor was the type of microorganism used in the fermentation process which is a single culture of Rhizopus oryzae, a single culture of Saccharomyces cerevisiae, a single culture of Lactobacillus plantarum, and mixed culture of Rhizopus oryzae, Saccharomyces cerevisiae, and Lactobacillus plantarum. The observed parameter was water content, sugar content, protein content, HCN content, ash content, amylose, and amylopectinn levels, swelling power, and water absorption index. The resultshowsw that the modification of cassava flour with a combination of pregelatinization and fermentation methods did not produce new characteristics or was very different from each origin method.